Peptide-Mediated Biomineralization - B. JANAIRO, JOSE ISAGANI; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book describes recent advances in peptide-mediated biomineralization and how this method was able to create improved catalysts through minor tweaks in the system. The book is thorough in its discussion which will be appreciated by beginners such as advanced undergraduate students. The topics covered are very recent which will raise the interest of experts. The book is envisioned to become a "one-stop-shop" for peptide mediated biomimetic material synthesis by discussing the most recent and most relevant topics related to biomineralization. The book attempts to discuss biomineralization from different perspectives in order to provide a multi-disciplinary treatment to the subject. Aside from being a reference material, this book can also serve as a manual to guide researchers engaged in the field since the chapters contain sections describing experimental procedures. The book also contains high quality illustrations and images that will surely add depth and clarity in the discussion.
General Introduction -- Taxonomy of Biomineralization Peptides -- Creating Functional Nanomaterials by Mimicking Nature's Symmetry -- Enhanced Nanomaterials Through Simple Tweaks in the Microenvironment -- Bimetallic Nanomaterials and Biomineralization: Synergism in Action -- Outlook and Challenges.
Keywords: Ceramic materials; Materials; Bioorganic chemistry; Ceramics; Materials Engineering; Bioorganic Chemistry